Моделирование и численный анализ влияния оперативной коррекции на напряженное состояние большой берцовой кости - Бреславский, Дмитрий Васильевич; Конкин, Валерий Николаевич; Сукиасов, Владимир Георгиевич; Пустовойт, Б. А.; Баха, В. Ф. Яхья (НТУ "ХПИ", 2007)
The comparative analysis results of various ways of operative correction of tibia face-to-face deformation are presented. Calculations are executed by finite element method in three-dimensional statement. Criterion for comparison is the stress state level of bone by physiological loading.
Keywords: деформации нижних конечностей; физиологические нагрузки; остеотомии костей; хирургическая коррекция кости; нагруженность оперированной кости